(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article provides specific examples from the practice of the author’s work in the study of a foreign language in a technical university. The effectiveness of the use of various methods in the process of learning a foreign language in a non-philological university is substantiated.